Holistic Islamic Education Policy in Strengthening Students Character through the Study of Ashifatul Madzmumah at Pesantren Darul Falah Amtsilati - Rofik Zulkarnain; Sukarman; Imroatul Rofiah; Nur Faizah; Abdulasi Kalupae; Muhammad Ma'sum Ma'sum (Universitas Wahid Hasyim Semarang, 2026)
The moral decline among the younger generation in the globalization era poses a serious challenge for Islamic educational institutions in shaping students' character. Islamic boarding schools (pesantren) are required to develop intellectual, spiritual, and moral dimensions in an integrated manner. This study aims to examine the implementation of a holistic-based Islamic education policy in strengthening santri (student) character through the study of the book Ashifatul Madzmumah at Pondok Pesantren Darul Falah Amtsilati. Utilizing a descriptive qualitative approach, data were gathered through observation, in-depth interviews, and documentation involving the institution's leader (pengasuh), instructors (ustadz/ustadzah), and students (santri). The findings indicate that the holistic approach is implemented by integrating cognitive learning, affective cultivation, and the habituation of Islamic behaviors. The book Ashifatul Madzmumah serves as a medium for character education through routine syi'ir (poetry) recitation at the end of teaching and learning activities, helping students internalize moral values. Distinct from previous general studies, this research specifically highlights character internalization through alphabetically structured syi'ir within a holistic framework. The study concludes that the synergy of educational policy, moral habituation, and pesantren culture comprehensively shapes students' Islamic character.